2019
DOI: 10.1093/jn/nxz023
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Are Not Consistently Associated with Variability in Blood Lead Concentrations in Pregnant British Women

Abstract: Background During pregnancy lead crosses the placenta freely and can have adverse effects on the fetus, with the potential for lifelong impact on the child. Identification of dietary patterns and food groups in relation to measures of lead status could provide a more useful alternative to nutrient-specific advice to minimize fetal lead exposure. Objectives The aim of this study was to evaluate whether dietary patterns and foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…We found that eating more green vegetables (either home-grown (p = 0.21) or non-home-grown (p = 0.001)) was significantly associated with lower BLL for the cohort as a whole. The UK Avon Longitudinal Study of Parents and Children (ALSPAC) (n = 4285) also reported a positive association between consumption of more green vegetables and lower BLL (Taylor et al, 2019). Our UAS gardener group also demonstrated significant associations between eating more herbaceous fruit, e.g.…”
Section: Discussionsupporting
confidence: 54%
“…We found that eating more green vegetables (either home-grown (p = 0.21) or non-home-grown (p = 0.001)) was significantly associated with lower BLL for the cohort as a whole. The UK Avon Longitudinal Study of Parents and Children (ALSPAC) (n = 4285) also reported a positive association between consumption of more green vegetables and lower BLL (Taylor et al, 2019). Our UAS gardener group also demonstrated significant associations between eating more herbaceous fruit, e.g.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, some nutrients could modify the absorption and excretion of lead. Vitamin D and phosphorus intake were positively associated with the bone lead in the middle-to elderlyaged men (48). In contrast, dietary calcium and iron intake were inversely associated with blood lead levels in pregnant individuals (49,50).…”
Section: Discussionmentioning
confidence: 88%
“…Lead exposure from industrial uses and environmental contamination has dramatically decreased over the past decades in developed countries. Still, diet remains one of the primary daily lead sources in developed countries, with leafy vegetables the most significant contributor (48). A low lead level was continuously detected in the food supply despite the substantial decrease in lead levels over decades.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations